Development of the Brazilian drug market toward Africa: Myths, evidence and theoretical questions - Corentin Cohen (Journal of Illicit Economies and Development (JIED), 2019)
Using existing research and original data, I discuss the development of a transatlantic drug market between Brazil and West Africa and its implications on Brazil's development and drug trafficking value chain. After establishing milestones of the history of this traffic I show how a global market of protection and transatlantic networks emerged from the alliances between Latin American criminal actors and high level elites in West Africa. The second part of the article focuses on the high concentration of capital created by exportations of cocaine. I show how these global markets affect the actions of drug traffickers, namely their strategies and use of violence by analyzing the development of maritime trade and the centrality of ports in this economy. The last part of the article analyzes the market for drug mules in Sao Paulo and how the strategy networks adapt to balance their risks of failure with low cost Nigerians migrant mules. Finally, the articles shows how this market attracted cultists groups from Nigeria and connects Brazil with other illegal markets.
Keywords: 330; Markets; development; protection; patronage; drug mules; transatlantic